The invasion and impacts of the African sharptooth catfish (Clariidae: Clarias gariepinus) in the Malay Peninsula. (25th August 2022) - Low, Bi Wei; Liew, Jia Huan; Tan, Heok Hui; Ahmad, Amirrudin; Zeng, Yiwen; Yeo, Darren C. J.
Abstract: The African sharptooth catfish, Clarias gariepinus, is a globally invasive species with known severe impacts, including native species declines through ecological (e.g., competition, predation) and genetic interactions (e.g., hybridisation, introgression). The species was introduced to the Malay Peninsula in the late 1980s, and has since become widely established. In this study, we used structural equation models (SEMs) (habitat analyses) and stable isotope analyses (dietary analyses) to elucidate the determinants of C. gariepinus invasion success in streams of the Malay Peninsula and investigate potential impacts on native counterparts. Our SEMs indicate that C. gariepinus invasions were mediated by greater anthropogenic influences as well as environmental conditions associated with open streams (large channels, higher temperatures and lower canopy cover). Additionally, on the one hand, we find that invasions by C. gariepinus have led to substantial negative impacts on the native Asian walking catfish, Clarias batrachus, with the latter being displaced, or in some areas extirpated, from its characteristic open‐stream habitats. On the other hand, C. gariepinus invasions did not appear to impact the native forest specialist, Clarias leiacanthus . Stable isotope analyses showed that all three Clarias species were opportunistic, generalist feeders. There was substantial overlap in the diets of C. gariepinus and C. batrachus . However, C. leiacanthus generally assimilated comparatively greater volumes of aquatic macroinvertebrate prey, therefore reducing dietary overlap with introduced C. gariepinus . Our findings indicate that propagule pressure and exaptations probably have played a major role in facilitating C. gariepinus invasions in the Malay Peninsula. Furthermore, our results suggest that habitat competition may have acted synergistically with trophic competition to drive C. gariepinus impacts on native species, although this was mitigated by differentiation in ecological preferences. Our results help shed light on the general characteristics of invasive species, the mechanisms facilitating their proliferation, and the potential outcomes of biological invasions. These highlight the urgent need to manage the introduction, spread and impacts of invasive C. gariepinus in the Malay Peninsula and elsewhere in its invaded range.